Hubungan Status Gizi dengan Lama Rawat Inap pada Pasien Sindrom Koroner Akut: The Relationship Between Nutritional Status and Length of Hospitalization in Patients with Acute Coronary Syndrome - Salsabila, Iynaas Yumna; Mu’ti, Abdul; Rajibsman (ITKES Wiyata Husada Samarinda, 2024)
Acute Coronary Syndrome (ACS) is a disorder of heart function caused by atherosclerotic plaques that form in the coronary blood vessels. The condition generally requires more intense care and hospitalization. Good nutritional status in hospitalized patients is known to improve patient response to therapy, reduce the incidence of infection, complications, and shorten recovery time after illness. This study aims to determine the relationship between nutritional status and length of hospitalization in ACS patients at Abdul Wahab Sjahranie Hospital Samarinda. This study used an observational analytic design with a cross-sectional study approach. Sampling using purposive sampling technique and data obtained from medical records of patients with ACS at Abdul Wahab Sjahranie Hospital Samarinda for the period January 2021 - June 2022. There were 59 patients who met the inclusion and exclusion criteria. Bivariate analysis using the Chi-Square test. Analysis of the relationship between nutritional status and length of hospitalization in SKA patients obtained a p-value of 0.506. There is no relationship between nutritional status and length of hospitalization in ACS patients at Abdul Wahab Sjahranie Hospital Samarinda